Demand-driven biogas production from sugar beet silage in a novel fixed bed disc reactor under mesophilic and thermophilic conditions. (October 2017) - Terboven, Christiane; Ramm, Patrice; Herrmann, Christiane
Highlights: A novel fixed bed disc reactor design was tested for flexible biogas production. High methane yields of 449–462 LN  kgVS were reached at an OLR of 4 gVS  L −1  d −1 . Alteration of gas production through variable feeding was possible within minutes. Elevated punctual loadings led to up to 3.5-fold increased biogas production rates. Thermophilic process temperature was advantageous over mesophilic conditions. Abstract: A newly developed fixed bed disc reactor (FBDR) which combines biofilm formation on biofilm carriers and reactor agitation in one single system was assessed for its applicability to demand-driven biogas production by variable feeding of sugar beet silage. Five different feeding patterns were studied at an organic loading of 4 gVS  L −1  d −1 under mesophilic and thermophilic conditions. High methane yields of 449–462 LN  kgVS were reached. Feeding variable punctual loadings caused immediate response with 1.2- to 3.5-fold increase in biogas production rates within 15 min. Although variable feeding did not induce process instability, a temporary decrease in pH-value and methane concentration below 40% occurred. Thermophilic temperature was advantageous as it resulted in a more rapid, higher methane production and less pronounced decrease in methane content after feeding. The FBDR was demonstrated to be well-suited for flexible biogas production, but further research and comparison with traditional reactor systems are required.